(untitled) (Research, Society and Development, 2021)
Introduction: The physical performance demanded of the nitric oxide substrate is favored with the increase in the oxygen supply to the muscle tissue through bronchodilation and vasodilation caused by the metabolic action of NO. General Objective: The main objective of this article is the understanding of the metabolic process of nitric oxide in human physiology, covering the origin by which this substance is developed or acquired in the human body through the consumption of vegetable strain supplementation, generating the benefits for good performance in physical activities. Methodology: As a methodology of the conclusive parameters of this article, a bibliographic survey of the scientific literature was used. Results and Discussion: The expected results were to prove that it is possible to obtain great results in the functional performance in relation to physical activities in general, through the consumption of foods rich in nitrate. Conclusion: In fact, Nitric Oxide (NO) is extremely important in exercise physiology, as it is a substance that promotes relaxation of blood vessels and regulation of blood pressure, impossible in a greater flow of blood, oxygen and nutrients all over the body.